Marking of the proximal facial nerve stump for delayed repair after vestibular schwannoma removal: Označitev proksimalnega krna obraznega živca za odloženo rekonstrukcijo živca po odstranitvi vestibularnega švanoma - Rebol, Janez; Milojković, Vojin (Acta Medico-Biotechnica, 2021)
Objective: To investigate whether marking the facial nerve stump during surgery permits facial nerve reconstruction to be performed successfully at later surgical intervention.Case report: The patient was operated for a large residual vestibular schwannoma via the retrosigmoid approach and the facial nerve was injured during tumor removal. A metal clip was placed on a facial nerve stump to permit localization and identification at a later time. One month after the first operation nerve repair employing a sural nerve graft from the cerebellopontine angle to the mastoid portion of the facial nerve was performed through the translabyrinthine approach.Conclusion: Follow-up of facial function was carried up for more than two years. The patient achieved very good functional results, confirming that end-to-end facial nerve repair with an interposition graft with positive outcome can be successfully performed as a delayed procedure.
Keywords: facial paralysis; facial nerve; facial nerve graft; vestibular schwannoma